Principles of minimal cognition in smart slime molds and social bacteria - Castro García, Óscar (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
The perception of the environment as well as sensorimotor coordination of unicellularsorganisms competence as the foundation of a cognitive principle that goes beyond minimum metabolicprocesses. I study the recognition of the environment in case of slime mold and bacteria as significantlearning processes in differentiating between hostile environment or optimal and physical transformationsof each agency on the basis of received signals in both the membrane and within the agencies.Sensorimotor coordination mechanisms of metabolic adaptation expanded shapes. Some of these coordination mechanisms are linked to the perception with the environment through pulses, as temporal processing of signals.
Keywords: Umwelt; subjectual; enaction; haptic perception; Weber-Fechner Law; bio-fenomenology